2022
DOI: 10.1177/00219983221109330
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of optical, dielectric and mechanical properties of a new nanocomposite based on polyvinyl alcohol and layered double hydroxide

Abstract: In this work, films in the form of poly (vinyl alcohol)/Layered Double Hydroxide (PVA/LDH) nanocomposites were synthesized with different amount of LDH (0%; 4% and 6%), and characterized by X-ray diffraction (XRD), infrared spectroscopy scanning electron microscopy (SEM), impedance spectroscopy and UV-Vis-NIR spectroscopy. Different characterizations were used to investigate the electrical/dielectric, optical and mechanical properties of the nanocomposite films XRD and infrared spectroscopy results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The bands appear at energies lower than 1000 cm −1 owing to the vibration mode of M-O, and M-O-M [41]. Therefore, the bands at 475 and 588 cm −1 and the tiny band observed in the spectrum of 11 wt% LDH/blend film at 526 cm -1 are arising from the absorption of Fe-O, Zn-O, and/or Fe-O-Zn bonds, confirming the existence of Zn/Fe-LDH NP in the blend matrix [25,35]. It is observed that the relative intensities of the characteristic vibrational bands of the blend are decreased below 7.0 wt%, and then increased again.…”
Section: Ftir Spectral Analysismentioning
confidence: 60%
See 2 more Smart Citations
“…The bands appear at energies lower than 1000 cm −1 owing to the vibration mode of M-O, and M-O-M [41]. Therefore, the bands at 475 and 588 cm −1 and the tiny band observed in the spectrum of 11 wt% LDH/blend film at 526 cm -1 are arising from the absorption of Fe-O, Zn-O, and/or Fe-O-Zn bonds, confirming the existence of Zn/Fe-LDH NP in the blend matrix [25,35]. It is observed that the relative intensities of the characteristic vibrational bands of the blend are decreased below 7.0 wt%, and then increased again.…”
Section: Ftir Spectral Analysismentioning
confidence: 60%
“…The wideness and intensity of the band at these three positions change irregularly with increasing LDH NP content. A tiny band at 1640 cm -1 is attributed to the COOsymmetric stretching vibration [25]. The two bands observed at ∼1418 cm -1 and 837 cm -1 are assigned to the bending modes of the CH 2 and C-O groups, respectively [36].…”
Section: Ftir Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic chitosan hydrogel adsorbent may be easily separated using a magnet instead of centrifuges or filtrations. Additionally, the use of pricey and dangerous organic solvents is decreased when using the magnetic chitosan hydrogel adsorbent with extraction in an aqueous sample (Table 5) [11,12,17,31].…”
Section: Langmuir Isothermmentioning
confidence: 99%